2016
DOI: 10.1515/ceer-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Selected Trace Element Concentrations in Peat Used for Cosmetic Production – A Case Study from Southern Poland

Abstract: The aim of the study was to assess the concentration of selected trace elements in organic soils used as a source to obtain a unique peat extract for cosmetics production. Peat material for laboratory analysis were collected from fen peatland located in the Prosna River Valley (Borek village). Studied peatland is managed by “Torf Corporation” company as a source of material to obtain peat extract for cosmetics production. In the collected soil samples (four soil profiles) Zn, Cu and Pb concentrations were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The smallest amounts of mineral material admixtures were observed in endopedons, while in the surface soil horizons its content was even 5 to 7 fold higher. Increase of mineral material contribution in the surface organic horizons might be the result of periodic flooding of Prosna river, what was also reported by Glina (2016). In the layers with the highest admixture of mineral particles (sand mainly) also the bulk density values were high (Table 3).…”
Section: Soil Description and Selected Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…The smallest amounts of mineral material admixtures were observed in endopedons, while in the surface soil horizons its content was even 5 to 7 fold higher. Increase of mineral material contribution in the surface organic horizons might be the result of periodic flooding of Prosna river, what was also reported by Glina (2016). In the layers with the highest admixture of mineral particles (sand mainly) also the bulk density values were high (Table 3).…”
Section: Soil Description and Selected Propertiessupporting
confidence: 72%
“…Described part of peatland is operated by ,,Torf Corporation" company, as a source of peat for cosmetics production (Glina, 2016). Study area as shown in the Figure 1B is divided into two parts.…”
Section: 1study Areamentioning
confidence: 99%